The Interaction between FSC Certification and the Implementation of the EU Timber Regulation in Romania - GAVRILUT INES; HALALISAN AURELIU FLORIN; GIURCA ALEXANDRU; SOTIROV METODI (FORESTS, 2015)
This explorative study aims to shed light on the ways in which Forest Stewardship Council (FSC) certification interacts with the implementation of the EU Timber Regulation (EUTR) in Romania. To this end, the EUTR implementation process is examined, and the relationship between this implementation and FSC certification is explored. There is a particular focus on the extent to which certification has helped companies to comply with EUTR requirements. The study uses the analytical framework of Transnational Business Governance Interactions (TBGI) and a mixed research approach. It is found that FSC certification has to a large extent helped companies to prepare for and align with the EUTR’s requirements, in particular concerning risk assessment and risk mitigation procedures needed for a due diligence system (DDS), and in the context of a “policy vacuum” period related to EUTR implementation. Moreover, recent changes in the FSC standard make it theoretically in line with EUTR requirements. However, difficulties remain in relation to the lack of information, costs and bureaucracy associated with both EUTR implementation and FSC certification. Notably, in the absence of a monitoring organization, the establishment of a viable DDS is still problematic as many companies remain unprepared for developing their own systems. Finally, the EUTR and its risk management requirements may have partly fueled the increase in uptake of chain of custody (CoC) certification in Romania. However, due to the risk of CoC certificates including illegally sourced timber, this recent uptake in certification does not necessarily indicate improved sustainable forest management (SFM) or full compliance with EUTR.
Keywords: certification; FSC; Due diligence; EU Timber Regulation; policy; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Forestry; Romania